2020
DOI: 10.1002/ps.5767
|View full text |Cite
|
Sign up to set email alerts
|

Implications of elevated carbon dioxide on the susceptibility of the globally invasive weed, Parthenium hysterophorus, to glyphosate herbicide

Abstract: BACKGROUND The noxious annual herb, Parthenium hysterophorus L. (Asteraceae), is an invasive weed of global significance, threatening food security, biodiversity and human health. In South Africa, chemical control is frequently used to manage P. hysterophorus, however, concern surrounds increasing atmospheric CO2 levels, which may reduce the efficacy of glyphosate against the weed. Therefore, this study aimed to determine the susceptibility of P. hysterophorus to glyphosate (1L/ha: recommended) after being gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…To counteract to global warming issue, the application of pesticides in the future climate condition has gained global attention because even the slightest increase in herbicide tolerance will be a future liability. Most of the previous simulation studies report a reduced efficacy of herbicides under high CO 2 concentration [25][26][27]. At the same time, a neutral effect of elevated CO 2 concentration on herbicide efficacy against weeds has also been reported in rare cases [25,[28][29][30].…”
Section: Application Of Pesticides In Agriculturementioning
confidence: 93%
See 1 more Smart Citation
“…To counteract to global warming issue, the application of pesticides in the future climate condition has gained global attention because even the slightest increase in herbicide tolerance will be a future liability. Most of the previous simulation studies report a reduced efficacy of herbicides under high CO 2 concentration [25][26][27]. At the same time, a neutral effect of elevated CO 2 concentration on herbicide efficacy against weeds has also been reported in rare cases [25,[28][29][30].…”
Section: Application Of Pesticides In Agriculturementioning
confidence: 93%
“…These experiments proved an equally effective glyphosate activity at CO 2 concentration slightly higher than the ambient atmospheric level (380 ppm). However, further enrichment of CO 2 (above 600 ppm) was reported to diminish the glyphosate efficacy [26,27]. No generalization of the effect of elevated CO 2 levels on herbicide efficacy was concluded, but the susceptibility of weeds towards herbicide application is species-specific.…”
Section: Application Of Pesticides In Agriculturementioning
confidence: 99%
“…In this study, plants were grown under elevated [CO 2 ] for only one generation. On the other hand, in South Africa, Cowie et al (2020b) reported significant reductions in parthenium weed plant mortality by glyphosate (1 L ha −1 ) at elevated [CO 2 ] of 600 and 800 ppm relative to 100% mortality at ambient [CO 2 ] of 400 ppm. This study tested the glyphosate response under elevated [CO 2 ] on fifth-generation plants continuously acclimatized to these conditions (Cowie et al 2020b).…”
Section: Efficacy Of Chemical Controlmentioning
confidence: 99%
“…For example, biological control agents can be negatively affected by increased temperature (Omkar et al 2013;Hasan and Ansari 2016) and reduced humidity (Fauzi et al 1999), resulting in subsequent fluctuations in field population density (Dhileepan and Strathie 2009). Additionally, a recent focus on the effect of [CO 2 ] elevation has suggested adjusting current management regimes (Shabbir et al 2019a;Cowie et al 2020b;Shabbir et al 2020). Therefore, a thorough review of the biology, ecology, and management options of parthenium weed under various climate change scenarios is vital to future management decisions, as adequate modification is needed to meet these new climate-induced challenges.…”
mentioning
confidence: 99%
“…Several approaches have been implemented to address the invasion of P. hysterophorus within various savanna systems across South Africa, most notably chemical, mechanical and biological controls (Strathie et al, 2011;Cowie et al, 2018Cowie et al, , 2020b. Moreover, the recent development of an integrated national strategy in 2016, with biological control at the core, is promising but yet to offer any notable success in controlling P. hysterophorus, with the weed increasing its range by 480% over the past decade (Terblanche et al, 2016;Van Wilgen and Wilson, 2018).…”
Section: Introductionmentioning
confidence: 99%